How to embroider almost everything : a sourcebook of 500+ modern motifs & easy stitch tutorials : learn to draw with thread! /: a sourcebook of 500+ modern motifs & easy stitch tutorials : learn to draw with thread!. (2019) - Gratz, Wendi
No abstract available